A The Meaning Of Ikan Mas Arsik In Batak Toba Culture - Simaremare, Perawati; Marwanti (JURNAL GASTRONOMI INDONESIA, 2025)
Culture is the wealth of a nation and must always be preserved. "Ikan mas arsik" is a traditional dish commonly used in customary events among the Batak Toba tribe. The purpose of this review is to explore the meaning of "ikan mas arsik" in Batak Toba culture. The method used is a narrative review, analyzing several articles using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method through the stages of identification, screening, eligibility, and inclusion.The analysis results indicate that the cultural values shaping the system of social relationships or kinship in Batak Toba customs are "Dalihan Na Tolu" (Hula-hula, Dongan Sabutuha, Boru), and the philosophy of life motivating the Batak Toba tribe is "Hamoraon, Hagabeon, and Hasangapon." Additionally, "ikan mas arsik" holds significance in Batak Toba culture and is used in traditional events such as weddings, "mambosuri" (seven-month pregnancy celebration), "mangupa," "tardidi" (child baptism), "mambosuri" (seven-month pregnancy celebration), and "mamboan sipanganon tu tulang" (seeking blessings and prayers from the maternal uncle or brother).This review not only contributes to the references on Batak Toba culture but also serves as input for related parties to preserve and sustain these cultural values